Pattern of Factors Associated with Obesity in Young Adults of Ischemic Heart Disease: Obesity and Ischemic Heart Diseaee - Tariq Abbas; Badar; Zarlish, Qazi Muhammad; Momin Rasheed; Kashif Ali Hashmi; Hira (Medical Journal of South Punjab, 2023)
Abstract:Objectives:    The objective of studying the pattern of factors associated with obesity in young adults with ischemic heart disease is to identify the various factors that contribute to the development of obesity in young adults that leads to ischemic heart disease in the population. By understanding the associated factors, healthcare providers can develop effective strategies for preventing and treating obesity in young adults with ischemic heart disease, which may ultimately help reduce their risk of heart disease and improve their overall health outcomes.Methodology: To better understand the pattern of risk factors responsible for obesity in young adults, we have conducted a cross-sectional in outpatient department (OPD) of Ch. Pervaiz Elahi Institute of Cardiology Multan. A non-purposive sampling technique was used. We have measured height, weight, body mass index BMI and collected data about their lifestyle, hypertension, diabetes and smoking status. Results: Out of 458 patients, after dichotomizing the BMI variable into >30 BMI as obese and